Fundamentals of accounting : volume I - Cabrera, Ma. Elenita Balatbat; Ledesma, Ester Francisco ;Lupisan, Ma. Conception Yamat (Manila, Philippines : GIC Enterprises & Co. Inc., 2010)
This textbook is written for use in the introductory course in Accounting under the Revised Curriculum for Accountancy Education effective school year 2007-2008.
CHAPTER 1. Introduction: Accounting and its environment -- 2. History and contemporary development in accounting -- 3. Role of accounting in business -- 4. Communication through financial statements -- 5. Conceptual framework for financial accounting -- 6. Introduction to accounting information system and the accounting cycle -- 7. Analyzing and summarizing business transactions of a service entity -- 8. Recording business transactions -- 9. Measuring business income: the adjusting process -- 10. Completing the Accounting cycle and Financial reporting of a service entity -- 11. Accounting for merchandising activities -- 12. Special journals and subsidiary ledgers -- 13. Completing the accounting cycle for a merchandising business -- 14. Basic Accounting for manufacturing operations.
Keywords: ACCOUNTING